A Hierarchical Fuzzy Comprehensive Evaluation Algorithm for Running State of a 6 kV (10 kV) Power Switch Cabinet. (22nd May 2018) - Wang, Fuzhong; Han, Sumin; Cao, Bin
Abstract : Considering the existence of many actual influential factors of a high voltage switch cabinet in the coal mine, the paper proposes a hierarchical fuzzy comprehensive evaluation algorithm to assess the running state of the 6 kV (10 kV) power vacuum switch cabinet better and improve operational safety and reliability of the power supply system. The algorithm can realize the state evaluation of bus bars, vacuum circuit breakers, electrical cables, other components, and the switch cabinet by the bottom-up approach. The running state evaluation index system and mathematical model of the switchgear are introduced particularly. According to the different forms of data information, this algorithm comprehensively evaluates the running state of the high voltage switchgear by using the online running data, test data, equipment information, and historical data records of the distribution cabinet. The actual operation states and test data of a handcart switch cabinet are taken as examples to prove the effectiveness of the algorithm.